RELEVANSI METODOLOGI TAfSIR KONTEMPORER (STUDI ATAS PEMIKIRAN MUHAMMAD THALBI) - Nihayah Abdurrahman (el-'Umdah, 2018)
The main problem of interpretation is actually the giving of meaning and production of meaning, however, Muhammad Thalbi views the nature of interpretation, for Muhammad Thalbi the nature of interpretation is how an interpreter is able to fnd authentic meaning from a text through the socio-historical context then, then catching the aspect of the moral ideal to contextualize the meaning in the present era with the new methodology, the Qur’an must be seen as if it had just come down yesterday and the Prophet had just greeted us. This is in line with what was revealed by Thalbi that the new age also requires interpretation with a perspective that is open to renewal. With a historical approach that is ?avored with a humanist perspective, he encourages a more open interpretation of the Qur’an through what he calls the approach (Qirâ ‘at Tar? khiyah)